2015
DOI: 10.1111/jjns.12095
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Job Rotation Stress Scale development and psychometric evaluation

Abstract: The NJRS can be considered a reliable and valid scale for the measurement of nurse job rotation stress for nursing management and research purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 22 publications
(29 reference statements)
1
20
0
Order By: Relevance
“…These results support the construct validity of the scale. The factor loadings in this study are found to be similar to the factor loadings in the original study (Huang, ).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…These results support the construct validity of the scale. The factor loadings in this study are found to be similar to the factor loadings in the original study (Huang, ).…”
Section: Discussionsupporting
confidence: 84%
“…NJRS: This scale was developed by Shan Huang et al. It includes 10 items and three subscales: (i) Emotional Response includes items 1, 2, 3, and 4; (ii) Communication includes items 8, 9 and 10; and (iii) Daily Life includes items 5, 6, and 7.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study used the Korean version of the nurse job rotation stress measurement tool developed by Huang et al . () and adapted by Yang et al . () to match the circumstances of Korean society.…”
Section: Methodsmentioning
confidence: 99%
“…In 2004, a study investigated job rotation among nurses in a hospital in Finland and discussed the need of both theoretical and empirical research on job rotation in this setting as it was rarely applied in hospitals (Järvi & Uusitalo, 2004). Since then, there has been a focus on examining job rotation among nurses working in hospitals with a primary quantitative approach using questionnaires (Chen et al, 2015;Dinis & Fronteira, 2015;Ho, Chang, Shih, & Liang, 2009;Huang et al, 2016;Järvi & Uusitalo, 2004;Mohan & Gomathi, 2015;Pan, Huang, Lee, & Chang, 2012). This existing research differs in terms of frequency, volition, time frame, involved departments, research focus and methods.…”
Section: Job Rotation Among Nurses In Hospitalsmentioning
confidence: 99%